Tanaidaceans from Brunei, V. The Leptocheliidae (Crustacea: Peracarida: Tanaidacea), with four new species - Bamber, Roger N.; Marshall, David J. (Zootaxa, 2015)
Leptocheliid material from sublittoral sandy substrata in the South China Sea off the coast of Brunei has been analyzed. Four species, all new to science, are described, all apparently interstitial in habitat. One is the second species to be described in the genus Catenarius (C. magdae); the others represent three new genera, one in each of the subfamilies Konariinae (Brunarus colekanus), Catenariinae (Ektraleptochelia phoxops) and Leptocheliinae (Nuberis areolaticola). As a result of the new information on the morphology of catenariins, the Andaman Sea species Leptochelia elongata is transferred to a new genus (Larsmentia) in the Catenariinae.